Shamanic Microscopy: Cellular Souls, Microbial Spirits. (4th March 2018) - Giraldo Herrera, César E.
Abstract: In Amerindian ontologies, hallucinations or visions, rather than being dismissed as delusions or symbolic constructs, are recognized as means of perceptual access to physical reality. Lowland South American shamans claim to be able to diagnose and treat infectious diseases, and to assess the status of wildlife resources through interactions with pathogenic agents perceived in visions. This essay examines some perceptual capabilities that shamans might be employing to explore their physical reality. The structure of the eye affords a form of microscopy of retinal structures and of objects flowing within them, including cells and microbial agents during systemic infection. Lowland South American shamanic practices involve optical and physiological conditions that optimize entoptic microscopy. Images of those visions display the characteristic features of shadow formation, confirming their microscopic origin. This phenomenological access to the microscopic world and similarities with the panorama depicted by current microbiology indicate the commensurability of these forms of knowledge.